Exploring advertiser's expectations of advertising agency services. Issue 6 (1st November 2016) - Turnbull, Sarah; Wheeler, Colin
Abstract : Advertisers have expectations about what they will receive from an advertising agency. These expectations are about the future service they believe the agency will deliver and influence the satisfaction/dissatisfaction the advertiser has of agency performance. Using an expert sample and a native categories approach, the study explores advertiser's expectations of agency services at the selection stage. The paper makes three main contributions to our understanding of agency selection. First, we provide insight into what advertisers seek to gain from an agency in future service delivery. Second, we identify four categories of expectations: craft, affinity, functionality and perspective. Third, we illustrate the nature of these expectations and provide evidence that some expectations are less precise than others. We consider the implications of the findings for the agency selection literature and agency management.